2017
DOI: 10.3389/fmed.2017.00008
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of the Quercetin in the Jejunal Myenteric Innervation of Diabetic Rats

Abstract: PurposeEnteric glial cells (EGCs) exert a critical role in the structural integrity, defense, and metabolic function of enteric neurons. Diabetes mellitus is a chronic disease characterized by metabolic disorders and chronic autonomic neuropathy. Quercetin supplementation, which is a potent antioxidant, has been used in order to reduce the effects of diabetes-induced oxidative stress. The purpose of this research was to investigate the effects of quercetin supplementation in the drinking water at a daily dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 56 publications
(50 reference statements)
3
18
2
1
Order By: Relevance
“…Correspondingly, the change in c‐fos, an indicator of activated EGCs, was also consistent with that found in EGCs. These findings contrast with those noting injury of EGCs during diabetic disease pathology; this difference is likely due to the involvement of different tissue segments and the nerve plexus used in experiments, as reports have demonstrated that there are variations in the effect of diabetes in different regions and plexus of the GI tract . However, several studies have provided evidence in favor of our results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the change in c‐fos, an indicator of activated EGCs, was also consistent with that found in EGCs. These findings contrast with those noting injury of EGCs during diabetic disease pathology; this difference is likely due to the involvement of different tissue segments and the nerve plexus used in experiments, as reports have demonstrated that there are variations in the effect of diabetes in different regions and plexus of the GI tract . However, several studies have provided evidence in favor of our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Although ENS damage in diabetic animals has been reported in several studies, our results did not show significant changes in PGP9.5‐immunopositive cells in the ilea of rats 1, 4, 8, or 16 weeks after the induction of diabetes. Similar to our results, a previous study demonstrated that a longer period, up to 19 weeks, is necessary to cause total loss of neurons in the ilea of diabetic rats .…”
Section: Discussioncontrasting
confidence: 87%
“…Furthermore, CGRP has antioxidant and anti-inflammatory effects (22,33,34) . In this study, the reduction of VIP-IR varicosity areas may indicate the presence of inflammatory process in the ileum induced by the AR, which may lead to a decrease of production and release of this neuropetide (24,30) . Furthermore, NO induces the release of VIP in the myenteric plexus (35,36) , and both morphometric reductions may indicate correlations with decrease in the production of the neuronal NO and VIP.…”
Section: Discussionmentioning
confidence: 68%
“…In the ENS, neuronal NOS-derived NO acts as neurotransmitter, which mediates the relaxing components of bowel peristalsis (29) . These phenotypic changes may indicate a compensatory mechanism to either GI dysfunctions or neurons loss in order to balance its bowel activity closer to ideal (30) . However, in our study, the reduction of somatic area of the nNOS-IR myenteric neurons suggests a negative effect induced by the AR since no alterations were observed in the nitrergic density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation